2003
DOI: 10.1081/erc-120018680
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Correlation in Patients Who Have a Pre‐diagnosis of Thyroiditis Ultrasonographically

Abstract: Hypoechogenic, heterogeneous thyroid gland may be strongly related to thyroiditis, which does not have any specific radiological findings. The sonographic finding of generalized parenchymal abnormality should alert the clinician to consider diffuse thyroid disease as the underlying cause and FNAB should be performed and a follow-up examination of these patients must be continued due to the risk of neoplastic disease of thyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The inflammatory diseases of the thyroid gland are classified into three groups, that is, acute, subacute and chronic. [ 3 8 ] De Quervain's thyroiditis, also named giant-cell or granulomatous thyroiditis, is the subacute inflammation of the thyroid and constitutes nearly 3–6% of all thyroid diseases. [ 1 3 4 ] It is a nonspecific inflammation that generally appears 2 weeks after a viral upper respiratory tract infection and regresses spontaneously within 2–3 months.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory diseases of the thyroid gland are classified into three groups, that is, acute, subacute and chronic. [ 3 8 ] De Quervain's thyroiditis, also named giant-cell or granulomatous thyroiditis, is the subacute inflammation of the thyroid and constitutes nearly 3–6% of all thyroid diseases. [ 1 3 4 ] It is a nonspecific inflammation that generally appears 2 weeks after a viral upper respiratory tract infection and regresses spontaneously within 2–3 months.…”
Section: Discussionmentioning
confidence: 99%
“…The radiological-cytopathological correlation was an important tool in these cases. Aydin et al (11) showed that the true diagnosis rate of thyroiditis was increased up to 81.8% when US-guided FNAB was performed, while it was 4.5% with using only the clinical and laboratory findings.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and fifty-three consecutive patients with Hashimoto's thyroiditis, who were presented to our clinic between April 2002 and January 2004, were recruited. The diagnosis was made through presence thyroid peroxidase antibody (TPO-Ab) and ultrasonographic appearance (Aydin et al, 2003). Thirtyeight patients, who had the diagnosis of diabetes mellitus according to ADA criteria (Gabir et al, 2000), were excluded from the study.…”
Section: Subjectsmentioning
confidence: 99%